Descriptive and Thematic Analysis of Students' Perceptions of YouTube in Education - Kashif Ali Sabiri; Humayun r Manzoo (Universitas Sembilanbelas November Kolaka, 2022)
The integration of YouTube in education has made learning innovative in the 21st century. A study using descriptive and thematic analysis was conducted to analyze students’ perceptions about the usage of YouTube for learning, their corresponding usage patterns, and associated factors motivating them to use YouTube.An online google survey was disseminated to undergraduate and master degree students and out of 80 students in total, 76 responded. Unavailability of desktop and laptop computers caused a major decline in the use of YouTube in education. Most of the students used YouTube for various academic activities except for video sharing. Most of the students found YouTube a beneficial source for improving educational activities. The findings in the last four questions confirmed that most of the students will integrate YouTube in their future learning activities. The findings can contribute to improving the use of YouTube to benefit from other online video source platforms.